2019
DOI: 10.1111/anae.14572
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sufentanil vs. remifentanil in fast‐track cardiac surgery patients

Abstract: Summary We retrospectively compared patients receiving remifentanil with patients receiving sufentanil undergoing fast‐track cardiac surgery. After 1:1 propensity score matching there were 609 patients in each group. The sufentanil group had a significantly longer mean (SD) ventilation time compared with the remifentanil group; 122 (59) vs. 80 (44) min, p < 0.001 and longer mean (SD) length of stay in the recovery area; 277 (77) vs. 263 (78) min, p = 0.002. The sufentanil group had a lower mean (SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Fourth, the tolerance and hyperalgesia observed with remifentanil use were not considered in our study. These side effects have been reported to be dependent on the remifentanil dose, with ≤0.2 µg/kg/minute 30 but also 0.1 to 0.15 µg/kg/minute 31,32 recommended during general anesthesia. However, in the present study, the mean dose of 0.038 µg/kg/minute was much lower.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the tolerance and hyperalgesia observed with remifentanil use were not considered in our study. These side effects have been reported to be dependent on the remifentanil dose, with ≤0.2 µg/kg/minute 30 but also 0.1 to 0.15 µg/kg/minute 31,32 recommended during general anesthesia. However, in the present study, the mean dose of 0.038 µg/kg/minute was much lower.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the needs of early extubation and short ICU stay after transthoracic device closure of VSD, fast-track anesthesia technology was used in our center. The fast-track anesthesia technique, which means to help patients regain consciousness and spontaneous breathing as soon as possible, and usually tracheal extubation within 6 h after operation [ 15 18 ]. Fast-track cardiac anesthesia technology is not only an anesthetic measure to help patients recover quickly after the operation but also one of the improvement measures to accelerate the anesthesia management in the perioperative period of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…As for the type of opioid, there is no outstanding evidence that short-acting opioids, such as remifentanil, are preferable to long-term opioids (eg, sufentanil) in terms of respiratory function recovery and time to extubation in cardiac surgery. Although a retrospective study of 1,218 patients undergoing cardiac surgery with a fast-track protocol showed reduced mechanical ventilation time and postanesthesia care unit LOS with remifentanil compared with sufentanil (at the cost, as expected, of an increased postoperative need for analgesic drugs), 143 the metaanalysis by Rong et al 142 did not find differences among fentanyl, sufentanil, remifentanil, and morphine with regard to the investigated outcomes. It must be said that cardiac anesthesiologists are not completely immune to the "philosophy" of OFA.…”
Section: Opioidsmentioning
confidence: 91%